Aberrant Correlation Between the Default Mode and Salience Networks in Mild Traumatic Brain Injury - Liu, Yongkang; Wu, Wenzhong; Chen, Xiao; Wu, Minghua; Hu, Gang; Zhou, Guoxing; Wang, Zhongqiu; Chen, Rong (Frontiers in Computational Neuroscience, 2020)
Objectives: The specific intrinsic network correlation abnormalities in mild traumatic brain injury (mTBI) patients are poorly understood. Our objective is to compare the correlations among the default mode, salience, and central executive networks in patients with mTBI and healthy controls. Methods: This two-year prospective study included 32 acute mTBI patients and 37 healthy comparisons. We calculated the functional connectivity scores among the default mode, salience, and central executive networks. Then we conducted multilevel correlation analysis to investigate component correlations, global graph, and local functional connectivity changes. Results: Patients with mTBI showed significant increased functional connectivity between the anterior part of the default mode network and the salience network compared with controls (p=0.013, false discovery rate correction). Hyper-connectivity between the default mode and salience network was significantly positively correlated with the dimensional change card sort score in patients with mTBI (r=0.40, p= 0.037). The average path length of mTBI patients was significantly higher than that of controls (p=0.028). Conclusions: Aberrant functional coupling between the default mode and salience networks were identified in acute mTBI patients. Our finding has great potential to improve our understanding of the network architecture of mTBI.